THE IMPACT OF USING GADGETS ON EARLY CHILDHOOD IN SIDAMUKTI VILLAGE - Mustakim, Usep Saepul; Muliasari, Ajeng; Sumarni, Nunung; Mardiah, Diah; Fatimah, Hana (LPPM Institut Pendidikan Nusantara Global, 2023)
The formulation of the problem in this study is how to analyze the impact of using gadgets in early childhood. The research objectives to be achieved in this study are readers can use gadgets wisely, readers can reduce dependence on gadgets, to provide information about the impact of using gadgets on health and to provide information about gadgets. The research method used is a qualitative research method. Based on the results of research on the negative and positive impacts of using gadgets on children aged 6-12 years in Sidamukti Village, it can be concluded: 1). The positive impact of using gadgets on respondents is 5 children aged 6-12 years in Sidamukti Village, showing data for 2 children who show a positive impact, this is classified as a minority because the other 3 respondents have not shown a positive impact. 2). The negative impact of using gadgets on respondents was 5 children aged 6-12 years in Sidamukti Village, showing data for 3 children showing a negative impact, this is classified as the majority because 2 other respondents have shown a positive impact.